Effect of tribological parameters on scratch behaviour of unidirectional E-glass fibre reinforced polyester composite. (December 2013) - Mzali, S.; Mezlini, S.; Zidi, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Understanding the scratch behaviour of the composite materials is of primary importance. The scratch behaviour of glass fibre reinforced polyester composite was investigated. A new scratch device is designed and developed. Scratch tests at room temperature were carried out, using conical indenter and constant scratching velocity. The main aim of this study is to investigate the effects of tribological parameters on wear mechanisms and friction coefficient. Particularly, the effects of the normal load and the attack angle were presented. The different wear scenario of the composite material during the scratch test was deduced, then supported by an analysis of the glass fibre reinforced polyester composite wear modes using scanning electron microscopy (SEM) observations was performed. The correlation between tribological parameters and wear mechanisms was highlighted through the composite scratch map. Results were compared with those previously published associated with the metallic and the polymeric materials.